Hydration of Barium Monohydroxide in (H2O)1-3 Clusters : Theory and Experiment - Cabanillas Vidosa, Iván (2013)
The ionization energies (IEe's) of small BaOH(H2O)m clusters (m = 1-3), as generated in a laser vaporization-supersonic expansion source have been determined by laser photoionization experiments over the 3.65?4.55 eV energy range. Complementary ab initio studies show that the IEe's are in good agreement with computed adiabatic ionization energies, and that BaOH(H2O)m structures with a direct coordination of the Ba atom to water molecules are favored over those that are characterized by H-bonded networks involving H2O molecules and the OH group of BaOH. Additional calculations have been performed on the hydration energies for the most stable isomers of the relevant BaOH(H2O)1-3 clusters. A comparison is made between the closed-shell title system and the results of related theoretical studies on the open-shell alkali monohydroxides, which allows for an interpretation of the opposite trends that are found in the cluster size dependence of the vertical ionization energies for both series of systems, and highlights the role of the BaOH unpaired electron in its ionization process. Altogether, the present evidence suggests for the initial steps of the BaOH hydration process to be dominated by electrostatic and polarization interactions between the Ba+ and OH? ion cores, which become both increasingly solvated upon sequential addition of water molecules.